Radio frequency ice dielectric permittivity measurements using CReSIS data. Issue 3 (25th March 2016) - Stockham, M.; Macy, J.; Besson, D.
Abstract: We report on studies of the ice dielectric permittivity using 150–195 MHz radar depth sounding data accumulated by the Center for Remote Sensing of Ice Sheets group, based at the University of Kansas. In the context of astroparticle physics experiments aimed at understanding radio emissions from cosmic rays interacting in the Earth's polar regions, our goals for this study were twofold: (1) identify radio frequency wave speed polarization asymmetries in Antarctica and (for the first time) in Greenland and (2) directly extract the depth dependence of the radio frequency field attenuation length as well as map out the attenuation over a large area. We first examine asymmetries in the real part of the permittivity (index‐of‐refraction n = ε ′ ) using Center for Remote Sensing of Ice Sheets bedrock radar reflection data taken from a single location, but with different signal polarizations. These data indicate birefringence for flow parallel‐, versus perpendicular‐to the local ice‐flow direction, with the former corresponding to smaller index‐of‐refraction (i.e., faster wave speed). Second, we have investigated the imaginary part of the permittivity ( ε ′′ ) and extracted the depth dependence of the field attenuation length ( L α ∼ ε ′′ ), as well as estimated the depth‐averaged radio frequency attenuation length from data taken near the Greenland Ice Core Project site near Summit, Greenland. We obtain < L α > = 50 0 − 60 + 90 m based on calculated values in the 1000–2000 m ice depth interval to which we have sensitivity and extrapolated to the full depth, where the errors shown reflect our uncertainty in our extrapolation. We also observe the expected decrease in attenuation length with increasing depth/temperature. A depth‐averaged attenuation length is also extracted directly from the relative strengths of the observed bedrock versus surface returns over large regions of both Greenland and Antarctica. Key Points: Apparent radio frequency birefringent asymmetry is observed in polar ice CReSIS data can possibly be used to estimate depth‐dependent attenuation of polar ice near GRIP The expanse of the CReSIS data set might be used to generalize points #1 and #2 to other polar ice